Guidelines for Improving Service Quality for the Elderly in Hotel and Resort Accommodation in Nakhon Ratchasima - Suksutdhi, Thanasit (International Journal of Psychosocial Rehabilitation, 2020)
This motive of this paper is to fulfill the service quality for the elderly in hotels and resort places in Thailand. Some factors support to enhance the service quality in the hotel and resort for elderly that are brand prestige of package tour, elderly well-being perception and professional service of the tour guide. These factors enhance service quality and make the mind of their customers to revisit the hotel. These factors are independent variables, the intention to revisit the hotel is the dependent variable, and the elderly tourist satisfaction play as a mediating variable. In this paper, the quantitative research method is used in which online questionnaires-based survey is used to collect the data. For analysis, the structural equation modeling is used to investigate the variables with their hypothesis. The results of these investigations show that there is a significant impact of professional service of tour guides and elderly well-being perception on the intension to revisit the hotel. This paper is helpful for hotel management, strategy developers and also the state's authorities to understand the importance of customer-oriented strategies in this service industry, and also its valid information gives chance to future research to use its data in their future research and overcome its weakness. Like there is only work on elderly people rather than youth or other age groups in its analysis portion, and also there is a lack of a mixed method of research. These weaknesses may impact the reliability and authenticity of this data which can be overcome by the future researchers.